The good lord bird - McBride, James, 1957- (Riverhead Books, 2013)
Henry Shackleford is a young slave living in the Kansas Territory in 1857, when the region is a battleground between anti- and pro-slavery forces. When John Brown, the legendary abolitionist, arrives in the area, an argument between Brown and Henry's master quickly turns violent. Henry is forced to leave town -- with Brown, who believes he's a girl. Over the ensuing months, Henry, whom Brown nicknames Little Onion, conceals his true identity as he struggles to stay alive. Eventually Little Onion finds himself with Brown at the historic raid on Harpers Ferry in 1859, one of the great catalysts for the Civil War.